Bounded rationality and industrial organization - Spiegler, Ran. (New York ; Oxford : Oxford University Press, 2011)
Although the challenge of enriching the psychology of decision makers in economic models has been at the frontier of theoretical research in the last decade, there has been no graduate-level, theory-oriented textbook to cover developments in the last 10-15 years. Thus, Bounded Rationality and Industrial Organization offers a welcome and crucial new understanding of market behavior-it challenges conventional wisdom in ways that are interesting and economically significant, and which in the end effect the well-being of all market participants.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Consumer behavior; Decision making; Consumption (Economics) -- Psychological aspects; Industrial organization (Economic theory)